Effect of time of pruning and peeling on the bark yield of cinnamon (Cinnamomum verum J. Pres.) in Andaman and Nicobar Islands - D R Singh, R Sudha, I Jaisankar, V Damodaran (Journal of Spices and Aromatic Crops, 2010)
An experiment was conducted at Port Blair, Andaman and Nicobar Islands, to study theeffect of time of pruning and peeling on the yield of cinnamon (Cinnamomum verum)intercropped in an arecanut (Areca catechu) garden. Pruning and peeling was carried out at20 days interval from first week of June to August during both the years. The number ofbranches (31) and girth (19.98 cm) were significantly higher in 10th July pruning. Bark yieldtree-1 (both fresh and dry weight) was also significantly higher during 10th July (4.03 kgfresh and 1.22 kg dry weight) pruning indicating that this period is ideal for pruning andpeeling cinnamon in Andaman and Nicobar Islands.